LEARNING BEYOND THE CLASSROOM: WHATSAPP IN LANGUAGE LEARNING - Ali Wira Rahman; Amir Patintingan; Rizka Indahyanti (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2018)
This research is intended to increase space and time in learning English, where space and time for English is very difficult to find in Indonesia. Through Mobile applications, learning will be more exclusive so as to reduce psychological barriers and cut the gap between teachers and students. They will feel more confident in expressing their opinions. This lesson will also be more constructive, give each other feedback between students and students and lecturers with students. This research will begin with the observation process to determine the object and location of the research. The use of WhatsaApp in learning will be conducted outside the classroom by determining the regular schedule and consistently. Begin by creating a group of 5 students with low levels of English language skills. The feature to be used is voice comment/messaging. Speaking skills will be the focus of this research. The method to be used is a combination of quantitative and qualitative (Mixed Method). Observations and interviews as qualitative representations and measurements of audio / speaking duration represent quantitative. The results of the study indicate that the use of WhatsApp in supporting learning outside the classroom provides varied progress. The review is measured from several aspects, namely Gender, Duration, Personal Margin Duration, Total Duration and Overall Personal Average.